Participatory Research for Health and Social Well-Being - Abma, Tineke; Banks, Sarah; Cook, Tina; Dias, Sónia; Madsen, Wendy; Springett, Jane; Wright, Michael T. (Springer International Publishing : Imprint: Springer, 2019)
This textbook is a comprehensive guide for students interested in using participatory research to improve people's health and well-being. It is especially designed for those working in the fields of health and social welfare who are embarking on participatory research for the first time. It covers all phases in participatory research from "getting started," to "acting for change," "continuing the journey" and "articulating impact." Its unique format helps readers understand the essence of participatory research as a comprehensive approach for doing research which is underpinned by a set of fundamental values. The many real life examples of participatory research projects from around the world inspire readers to find creative ways to manage their own research while opening up new horizons in their work.